Engineering trustworthy software systems : first International School, SETSS 2014, Chongqing, China, September 8-13, 2014. Tutorial Lectures /: first International School, SETSS 2014, Chongqing, China, September 8-13, 2014. Tutorial Lectures. (2016) - Unknown
No abstract available